Age-related metabolic study of glioma brain using magnetic resonance spectroscopy. (2021) - Arshad Javid, Muhammad; Habiba, Ume; Ain Rashid, Quratul; Muhammad, Bilal
Abstract: The purpose of this study is to assess the aging effect of the most sensitive metabolite choline and its ratio with other metabolites N-acetyl aspartate, creatine, myoinositol and lactate in suggestive glioma brain using magnetic resonance spectroscopy. Forty-four suggestive glioma patients were scanned at 1.5 Tesla (G.E) from MRI center, Bahawalpur Victoria Hospital (BVH) Bahawalpur, Pakistan. The mean age of 44 patients was 41.40 years with S.D = 17.36 in which total 24 males (mean age = 39.1, S.D = 17.37, min = 09, max = 72) and 20 females (mean age = 44.1, S.D = 17.39, min = 15, max = 85). For chemical analysis, patients were categorized into three age groups, 16 patients in group-I (G-I) of age range 6–30, 18 patients in group-II (G-II) of age range 31–55 and 10 in group-II (G-III) of age range 56–85 in years. Single voxel spectroscopy (SVS) were employed using one STEAM technique to get 1H MRS Spectra. I.Q Lite software to demarcate the region of interest (ROI) in brain. Data analysis was performed in OrgionPro.8, China. A p-value (P ≤ 0.05) was deemed to be statistically significant in data. One-way AONVA test was used to compare the aged related variation of five metabolites in three age groups G-I, G-II and G-III. High peak of choline with lactate peak verified the malignancy in the suggestive glioma cases. The p-value (p > 0.5) of Ch/Cr was observed in G-I compare to the p-value (p > 0.05) of Ch/Cr for G-II and G-III during study. Statistically, results demonstrated no significant difference in three proposed age groups in the region of suggestive glioma brain. Statistically, it was concluded that age‐related metabolic changes in three proposed groups remained insignificant (p > 0.05) in region of glioma brain. However, higher choline ratio and reduced ratio of N-acetylaspartate revealed the higher progression of malignancy in G-II that might be monitoring marker of aging effect of metabolites.